Modelling and Analysis of Induction Motor using LabVIEW - E. Ramprasath; P. Manojkumar (Institute of Advanced Engineering and Science, 2015)
Induction motor characteristics became complex to study, after the invention of drives where the motor incorporated with power electronic switches such as thyristor, diodes, GTO, and MOSFET. Induction motor characteristics can be studied and modelled with software such as Finite Element Analysis and Laboratory Virtual Instrument Engineering Workbench. Finite Element Analysis is used to study and model the motor might be complex and the time taken to compute was unreliable. In this paper induction motor was modeled with the help of LabVIEW software this allows us to model and simulate the motor in order to analyze the performance. The induction motor modelled here was based on the mathematical equations.